Correlation of Clinical Frailty Scale Assessment and in-Hospital Mortality in Elderly Critically Ill Patients Admitted to Intensive Care Units of Private Sector Tertiary Care Hospital: Clinical Frailty Scale in Elderly Critically Ill Patients Admitted to Intensive Care Units - Muzaffar, Saima; Hashmi , Madiha; Rasheed, Ghulam; Jamil, Araj; Umer, Sughand; Kamran, Ali (Pakistan Journal of Health Sciences, 2025)
Frailty is a complex geriatric condition marked by increased vulnerability to adverse health events. In intensive care unit patients, there is a clear correlation between the Clinical Frailty Scale and higher short- and long-term mortality rates. Objectives: To evaluate the prognostic importance of frailty, measure the risk of death in the Intensive Care Unit for all Clinical Frailty Scale scores, and methodically evaluate the association between frailty and Intensive Care Unit mortality. Methods: This cross-sectional study was conducted over 1 year (Jan 2023 to July 2023) at the Department of Medical Intensive Care Unit of Ziauddin University Hospital, Karachi Pakistan. Irrespective of gender, all patients of age more than 60 years admitted to the Medical Intensive Care Unit were included. In this study, individuals ≥60 years of age had their pre-admission frailty and hospital mortality compared using the Clinical Frailty Scale. Results: The median age was 75 years. The overall mortality rate was 9.9%. The Clinical Frailty Scale score indicated that 29.7% of patients were classified as non-fragile, 18.7% as vulnerable or pre-fragile, and 51.6% as frail. A significant association of Clinical Frailty Scale assessment was observed with gender, age, outcome, Acute Physiology and Chronic Health Evaluation score and invasive (mechanical ventilation). According to multivariate logistic regression, patients on mechanical ventilators have a higher mortality rate. Conclusions: It was concluded that the findings demonstrated a strong correlation between mortality and the Clinical Frailty Scale among critically sick patients admitted to the intensive care unit.